Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find the particular solution using the method of undetermined coefficients:


share|cite|improve this question
up vote 1 down vote accepted

Your equation is $y''''+y'''=1-x^2e^{-x}$. Now change the $y'$ to $Dy$ form as follows. So $$y''''\to D^4y,\\ y'''\to D^3y,$$ So by new arranging respect to $D$ operator we get our equation as: $$D^4y+D^3y=1-x^2e^{-x}$$ or by factoring and expanding $$(D^4+D^3)y=D^3(D+1)y=1-x^2e^{-x}$$ Note that considering the corresponding homogeneous equation $$D^3(D+1)y=0$$ we get $D^3=0,\;\; (D+1)=0$ which leads us to write the general solutions as $$y_c(x) = c_1+c_2x+c_3x^2+c_4e^{-x}$$ But some facts:

  • If $y=\text{constant}$ so $y'=0$ or $Dy=0$. Here, the operator $D$ annihilates $y$ which is just a constant.($Dc=0$)
  • If $y=cx$ in which $c$ is a constant so $y''=0$ or $D^2y=0$. It means that the operator polynomial $P(D)=D^2$ annihilates $y=cx$. $(\text{or} \; P(D)=D^2(cx)=cD^2x=c(x'')=0)$. Generally, $D^{n+1}$ annihilates not only the function $y=cx^{n}$ but also all linear functions as $$y=c_0+c_1x+c_2x^2+...+c_nx^n$$ It means that $$P(D)y=D^{n+1}y=0$$.
  • As the same the differential operator $(D-\alpha)^n$ annihilates each of the following functions and every linear combinations of them: $$e^{\alpha x},xe^{\alpha x},x^2e^{\alpha x},...,x^{n-1}e^{\alpha x}$$ Now look at the RHS of your original equation. I mean $=1-x^2e^{-x}$. Can we guess of which proper differential polynomial annihilates it? As above it would be $D(D+1)^3$. $\;$ $D$ for $1$ and $(D+1)^3$ for $-x^2e^{-x}$. It means that $D(D+1)^3 \left(1-x^2e^{-x}\right)=0$.

Now we consider of what we have achieved at last: $$D^3(D+1)y=1-x^2e^{-x}$$ Put the operator $D(D+1)^3$ before both sides of the above converted equation: $$D(D+1)^3\left(D^3(D+1)y\right)=D(D+1)^3 \left(1-x^2e^{-x}\right)=0$$ or $$D^4(D+1)^4y=0$$ In fact, we have found a proper differential operator $P(D)=D^4(D+1)^4$ which if it effects to $y$, $y$ will be lost.

Now, for a while, forget our equation and look at $D^4(D+1)^4y=0$ and think someone gave this to us asking to guess which function $y$ may satisfy the equality above? We reply:

  • Since we have $(D+1)$ so we have some forms as $e^{-x}$ in $y$.
  • Since $(D+1)$ has a power $4$ so we have the forms $Ae^{-x},\; Bxe^{-x}, \;Cx^2e^{-x}, \; Ex^3e^{-x}$ in $y$. Note that you multiply $e^{-x}$, in the previous line, by $A,\; Bx,\; Cx^2,\; Ex^3$. (Exactly until the power of $x$ becomes $4-1=3$).

  • And, since we have $D^4$, then $y$ has the term $F,\; Gx,\; Hx^2,\; Lx^3$.

So we are done. Our probable function which satisfy the original equation is $$y=Ae^{-x}+ Bxe^{-x}+Cx^2e^{-x}+Ex^3e^{-x}+F+Gx+Hx^2+Lx^3$$. Now eliminate those terms which generate $y_c(x)$ above and take the rest for what we have looked for. After finding the $y_p(x)$, you should satisfy it into the equation for finding the unknown coefficients.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.